The RB1 Mutation Spectrum and Genetic Management Consultation in Pediatric Patients with Retinoblastoma in Beijing, China - Xie Y; Xu XL; Wei WB (Dove Medical Press, 2021)
Ying Xie,1,2 Xiao-Lin Xu,1 Wen-Bin Wei1 1Beijing Tongren Eye Center, Beijing Key Laboratory of Intraocular Tumor Diagnosis and Treatment, Beijing Ophthalmology and Visual Sciences Key Lab, Medical Artificial Intelligence Research and Verification Key Laboratory of the Ministry of Industry and Information Technology, Beijing Tongren Hospital, Capital Medical University, Beijing, 100730, People's Republic of China; 2Department of Opthalmology, Shanxi Provincial People's Hospital, Taiyuan, 030012, People's Republic of ChinaCorrespondence: Wen-Bin WeiBeijing Tongren Eye Center, Beijing Key Laboratory of Intraocular Tumor Diagnosis and Treatment, Beijing Ophthalmology and Visual Sciences Key Lab, Medical Artificial Intelligence Research and Verification Key Laboratory of the Ministry of Industry and Information Technology, Beijing Tongren Hospital, Capital Medical University, No. 1 of Dong Jiao Min Lane, Dongcheng District, Beijing, 100730, People's Republic of ChinaTel +86 10 5826 9516Fax +86 10 6512 5617Email weiwb1023@163.comObjective: The present study screened the structural mutations of the retinoblastoma (RB1) gene using gene capture and a preliminary exploration of the correlation between the genotypes and phenotypes.Methods: A total of 45 formalin-fixed paraffin-embedded (FFPE) tissue samples and 12 peripheral venous blood samples from patients with retinoblastoma (RB) confirmed by pathological examination at Beijing Tongren Hospital were collected between May 2019 and May 2021. DNA from the samples was extracted, sequenced, and analyzed to detect the mutations in the RB1 gene by designing the targeted capture probes for exons and the flanking sequences of the gene.Results: Of the 45 FFPE tissue samples, 23 were from male patients and 22 were from female patients, all aged between 4 months and 10 years, with an average age of 2.5 ± 1.3 years. Two of these patients had bilateral RB and 43 had unilateral RB (23 in the right eye and 20 in the left eye). Of the 12 peripheral venous blood samples, 7 were from male patients and 5 were from female patients, all aged between 8 months and 4 years, with an average age of 1.3 ± 0.9 years. Two of these patients had bilateral RB and 10 had unilateral RB (8 in the right eye and 2 in the left eye). Three de novo pathogenic mutations were found in the FFPE tissues, along with one de novo potentially pathogenic mutation, while three de novo potentially pathogenic mutations were found in the blood samples.Conclusion: Gene capture is a low-cost and efficient method for the gene sequencing of RB. A total of seven de novo mutations were identified through mutation testing of the pathogenic gene RB1 in 56 pediatric patients with RB. This complemented the mutation spectrum of the RB1 gene and helped to improve the molecular diagnosis of RB, thereby providing a basis for genetic counseling and prediction of the clinical phenotype, as well as for the genetic testing of the offspring of patients with RB.Clinical Registration Number: ChiCTR-EPC-17013892.Keywords: retinoblastoma, RB1 gene, gene capture